2021
DOI: 10.1101/2021.02.07.430123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selection and structural characterisation of anti-TREM2 scFvs that reduce levels of shed ectodomain

Abstract: Single point mutations in TREM2, a receptor expressed by microglia in the brain, are associated with an increased risk of neurodegeneration including Alzheimer's disease. Numerous studies support a role for TREM2 in sensing damaging stimuli and triggering signalling cascades necessary for neuroprotection. Despite its significant role, ligands and regulators of TREM2 activation, and the mechanisms governing TREM2-dependent responses and its cleavage from the membrane, remain poorly characterised. Here, we prese… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The precise mechanisms through which sTREM2 shedding influences TREM2 receptor signaling and the inherent functions of sTREM2 remain somewhat enigmatic. It has been observed that stabilizing TREM2 on the cellular membrane with antibodies to hinder its proteolytic shedding by sTREM2 enhances not only downstream TREM2 signaling but also critical functions of the receptor, such as the phagocytic activity of microglial cells (Schlepckow et al, 2020;Szykowska et al, 2021). This observation suggests that the detachment of TREM2 from the membrane, facilitated by ADAM metalloprotease activity leading to sTREM2 production, might play a regulatory role in attenuating TREM2 receptor signaling.…”
Section: Strem2 Dynamics and Alzheimer's Disease Progressionmentioning
confidence: 99%
“…The precise mechanisms through which sTREM2 shedding influences TREM2 receptor signaling and the inherent functions of sTREM2 remain somewhat enigmatic. It has been observed that stabilizing TREM2 on the cellular membrane with antibodies to hinder its proteolytic shedding by sTREM2 enhances not only downstream TREM2 signaling but also critical functions of the receptor, such as the phagocytic activity of microglial cells (Schlepckow et al, 2020;Szykowska et al, 2021). This observation suggests that the detachment of TREM2 from the membrane, facilitated by ADAM metalloprotease activity leading to sTREM2 production, might play a regulatory role in attenuating TREM2 receptor signaling.…”
Section: Strem2 Dynamics and Alzheimer's Disease Progressionmentioning
confidence: 99%